Find the value of the expression above for all .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Recall the infinite series definition of e x : e x = n = 0 ∑ ∞ n ! x n = 1 + 1 ! x + 2 ! x 2 + 3 ! x 3 + ⋯ The sum seems very similar to the one being multiplied by e x . In fact, if we input − x in place of x : e − x = n = 0 ∑ ∞ n ! ( − x ) n = n = 0 ∑ ∞ n ! ( ( x ) ( − 1 ) ) n = n = 0 ∑ ∞ n ! x n ( − 1 ) n We get the sum in our expression! Substituting it with e − x we get e x e − x = e 0 = 1